Confluence of Multidisciplinary Sciences for Polymer Joining - Vendan, S. Arungalai; Natesh, M.; Garg, Akhil; Gao, Liang (Springer Nature Singapore : Imprint: Springer, 2019)
This book offers a systematic overview of polymer joining and highlights the experimental and numerical work currently being pursued to devise possible strategies to overcome the technical issues. It also covers the fundamentals of polymers, the corresponding joining processes and related technologies. A chapter on the extrapolation of finite element analysis (FEA) for forecasting the deformation and temperature distribution during polymer joining is also included. Given its breadth of coverage, the book will be of great interest to researchers, engineers and practitioners whose work involves polymers.